Laboratory-scale study of a biodegradable microplastic polylactic acid stabilizing aerobic granular sludge system. (1st August 2022) - Song, Xin; Sun, Shiquan; Gao, Yang; Zhang, Wei; Zhou, Lean; B, Jiang C.; Wan, Junli; Chen, Jing; Zhou, Lu; Yu, Guanlong
Abstract: The effects of microplastics on aerobic granular sludge technology are an emerging issue, although the impact of degradable microplastics (DMPs) on the aerobic granular system is still unexplored. In this study, degradable microplastic polylactic acid (DMP-PLA) was added at three concentrations (5, 15, 40 mg/L), which strengthened the granular stability and consequently stabilized pollutant removal compared to the control (without DMP-PLA). The experiment showed that adding DMP-PLA made cells secrete more extracellular polymeric substances [64.8 mg/g MLVSS (mixed liquor suspended solids)], particularly retaining β-D-glucopyranose polysaccharides in experimental group. In addition, abundant hydrogen bonds were also maintained. The reactor under the stress of DMP-PLA exhibited high pollutant removal efficiency (COD>88%, TP>91%, TIN>86%), indicating high performance of the microbes. Microbial analysis at the genus level indicated that Defuviicoccus and Candidatus_Competibacter were dominant after DMP-PLA addition, which identified denitrifying glycogen-accumulating organisms as beneficial for nitrogenous compound removal. Redundancy analysis showed that the abundance of Candidatus_Competibacter was positively related to the addition of DMP-PLA. This study demonstrated that DMP-PLA was feasibly employed in the aerobic granular water treatment process, and presents a new method to optimize the stability and extracellular secretion of the microbial community. Graphical abstract: Image 1 Highlights: The addition of DMP-PLA is beneficial for granular stabilization. DMP-PLA makes EPS full of abundant hydrogen bonds. β-D-glucopyranose polysaccharides were retained in aerobic granular sludge.